Publishing child development research from around the world: An unfair playing field resulting in most of the world's child population under‐represented in research - Draper, Catherine E.; Barnett, Lisa M.; Cook, Caylee J.; Cuartas, Jorge A.; Howard, Steven J.; McCoy, Dana C.; Merkley, Rebecca; Molano, Andres; Maldonado‐Carreño, Carolina; Obradović, Jelena; Scerif, Gaia; Valentini, Nadia C.; et al. (Infant and child development, 2023)
It has become increasingly apparent that publishing research on child development from certain countries is especially challenging. These countries have been referred to collectively as the Majority World, the Global South, non‐WEIRD (Western, Educated, Industrial, Rich, and Democratic), or low‐ and middle‐income countries. The aim of this paper is to draw attention to these persistent challenges, and provide constructive recommendations to contribute to better representation of children from these countries in child development research. In this paper, we outline the history of publication bias in developmental science, and issues of generalization of research from these countries and hence where it ‘fits’ in terms of publishing. The importance of explaining context is highlighted, including for research on measurement child development outcomes, and attention is drawn to the vicious publication‐funding cycle that further exacerbates the challenges of publishing this research. Specific recommendations are made to assist child development journals achieve their stated goals of creating a more inclusive, equitable, diverse, and global field of child development.